PENGARUH CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING FINANCING (NPF), RETURN ON EQUITY (ROE) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP PERTUMBUHAN PROFITABILITAS SEBELUM DAN SESUDAH PEMISAHAN - Anggi Suryani; Irfan Irfan; Muttaqien Muttaqien (LPPM STIE Lhokseumawe, 2019)
This study aims to determine and analyze the effect of profitability growth before and after separation at Bank Syariah Aceh. The difference in the level of health at Bank Aceh Syariah before and after separation using the ratio of capital adequacy ratio (CAR), non-performing financing (NPF), return on equity (ROE) and loan to deposit ratio (LDR). This study uses an 8-year period, namely 2012-2019 by using quarterly financial reports. The analytical method used is a multiple linear regression model using eviews. The dummy variable is used to determine whether Bank Aceh Syariah health differences occur before and after separation. The results of the analysis show that CAR and ROE have an effect on profitability growth, while NPF and LDR have no effect on profitability growth. In addition, the dummy results show there are differences in Bank Syariah Aceh before and after separation.